Neraca Kehidupan Spodoptera pectinicornis (Hampson) dengan Pakan Gulma Kayu Apu Pistia stratiotes Linn yang diberi Pupuk NPK dan AB Mix - Indar Pramudi, Muhammad; Komala Sari, Kurnia; Soedijo, Samharinto (Rawa Sains: Jurnal Sains STIPER Amuntai, 2022)
This study aims to examine the life balance of the biological control agent Spodoptera pectinicornis fed Pistia stratiotes with NPK and AB mix fertilization.. The research was carried out from March to May 2021 at the Laboratory Pengendalian Hayati and Greenhouse Entomology Faculty of Agriculture University Lambung Mangkurat Banjarbaru. The data in this study were analyzed descriptively by calculating the population. S. pectinicornis in one life cycle. There are 3 treatments and 3 replications on the 100 egg s. pectinicornis, The highest gross reproductive rate (GRR) was in the AB mix treatment of 1912 individuals/generation. The highest net reproduction rate (Ro) was found in the AB mix treatment of 129.520. The average value of the shortest generation period (T) in the NPK fertilizer treatment was only 26.334 days. The highest intrinsic growth rate (r) was found in the AB mix fertilizer treatment of 0.164 individuals/parent/day. The calculation of the limited growth rate (λ) showed that the AB mix treatment had the highest population increase of 1,174 individuals/parent/day. Apu wood treated with NPK and AB mix fertilizers can increase the rate of population development in the life table of the insect S. pectinicornis.